Effects of COVID-19 convalescence on pregnancy outcomes in frozen-thawed embryo transfer: A retrospective cohort study - Liwen Shen; Xiaoqin Pan; Yurong Zhu; Luping Liu (PLoS ONE, 2025)
In this study, we aimed to examine whether frozen-thawed embryo transfer during the recovery period after coronavirus disease can affect treatment outcomes. This population-based retrospective cohort study included patients who underwent frozen-thawed embryo transfer in the first cycle and did not have a history of coronavirus disease (n = 355, control group) or recovered from coronavirus disease within 6 months (n = 185) or 6–12 months (n = 230). Univariate analysis was performed to determine significant associations between the baseline variables, frozen-thawed embryo transfer cycle characteristics, clinical pregnancy rates, ongoing pregnancy rates, and pregnancy complication rates. Variables with significant associations in the univariate analysis were included in the multivariate logistic regression analysis to identify the effect of baseline characteristics, frozen-thawed embryo transfer cycle characteristics, and history of coronavirus disease on clinical pregnancy, ongoing pregnancy, and pregnancy complication rates. Patients who recovered from coronavirus disease within 6 months were more likely to experience complications during pregnancy than control group patients (33.7% vs. 20.3%, p = 0.001). Multivariate logistic regression analysis confirmed that a history of coronavirus disease within 6 months (odds ratio: 2.34, 95% confidence interval: 1.93–4.58) was a risk factor for pregnancy complications; however, a history of coronavirus disease was not a risk factor for clinical pregnancy rate, ongoing pregnancy rate, human chorionic gonadotrophin positivity rate, abortion rate, or live birth rate. Frozen-thawed embryo transfer can be conventionally performed during the recovery period after coronavirus disease; however, enhanced monitoring and follow-up during pregnancy are necessary to ensure the safety of the entire pregnancy and delivery process.